1996
DOI: 10.1042/cs090008pa
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cytokine Profiles in Patients with Idiopathic Dilated Cardiomyopathy and Their Asymptomatic Relatives

Abstract: Objectives-Immunological abnormalities in idiopathic dilated cardiomyopathy (DCM) include an increase in soluble interleukin(IL)-2 receptor, disease specific cardiac autoantibodies, an HLA-DR4 association, and familial aggregation of disease; however, cytokine profiles have not been defined. Serum concentrations of IL-2, IL-4, IL-10, and IL-12 were measured in patients with DCM (WHO criteria), relatives with asymptomatic left ventricular enlargement (LVE), patients with ischaemic heart failure (IHD), and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…40 Serum levels of IL-10 were elevated in some patients with DCM, but not in patients with ICM. 40 However, in the present, the background diseases of CHF did not affect the serum levels of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…40 Serum levels of IL-10 were elevated in some patients with DCM, but not in patients with ICM. 40 However, in the present, the background diseases of CHF did not affect the serum levels of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the development of DCM is accompanied by increased circulating levels of these specific cytokines. 37,38 Thus increased levels of specific cytokines with the development of DCM may modulate MMP species abundance. The MMPs are a family of metalloproteinases in which catalytic activity is influenced by substrate product stoichiometry.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the enhancement and activity of IL-4 in DCM patients, and clarified the absence of detectable IL-4 in both myocardium and circulation of DCM patients [20,21]. Although IL-13 is a novel cytokine sharing a number of biological properties with those of IL-4, the differential functions of IL-13, but not of IL-4, have been recently reported in various inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%